Risk factors analysis for significant liver fibrosis of prenatally diagnosed choledochal cysts: a retrospective case-control study - Zhuang, XiaoJin; He, YuanBin; Wu, DianMing; Fang, YiFan; Lin, Yu; Huang, YanBing (Frontiers in Pediatrics, 2025)
BackgroundThe severity of liver fibrosis and optimal surgical timing in infants with prenatally diagnosed choledochal cysts (CDCs) remain contentious. This study aims to identify risk factors for significant liver fibrosis in prenatally diagnosed CDCs and guide optimal surgical timing.MethodsThis retrospective case-control study reviewed infants with prenatally diagnosed CDCs between January 2016 and January 2024. Liver fibrosis was staged (S0–S4) using the Batts-Ludwig system. Infants were categorized into mild/no fibrosis (<S2) and significant fibrosis (≥S2) groups based on histopathology. The aspartate aminotransferase to platelet ratio index (APRI) and Fibrosis-4 index (FIB-4) were validated, and multivariate logistic regression analyses were performed to identify independent risk factors. The receiver operating characteristic (ROC) curve was used to assess diagnostic performance.ResultsA total of 50 infants (20 male, 30 female) were enrolled, with a median gestational age at diagnosis of 28 weeks (range: 19–39 weeks) and a median surgical age of 54 days (range: 7–360 days). Liver fibrosis was present in 40 cases (80%), with 34 cases (68%) classified as <S2 and 16 cases (32%) as ≥S2. Univariate analysis showed that infants with significant liver fibrosis had a higher proportion of clinical symptoms and Type IV CDCs, as well as elevated AST, TBil, DBil, GGT, WBC, and cysts width before surgery (p < 0.05). Multivariate logistic regression analysis identified Type IV CDCs (OR = 11.39, 95% CI: 1.04–124.65) and GGT (OR = 1.003, 95% CI 1.00–1.01) as independent influencing factors (p < 0.05). For diagnosing significant fibrosis (≥S2), GGT demonstrated an area under the ROC curve (AUROC) of 0.86, with an optimal cutoff of 327 U/L (sensitivity: 75%, specificity: 88%). APRI showed an AUROC of 0.76 (95% CI 0.61–0.92, p < 0.01) with an optimal cutoff of 0.23 (sensitivity: 75%, specificity: 80%).ConclusionLiver fibrosis is common in infants with prenatally diagnosed CDCs, primarily presenting as mild. Type IV CDCs and GGT > 327 U/L are significant risk factors, highlighting the need for close monitoring and timely surgical intervention.